O ambiwalentnym humorze Karla Michala - Czernikow, Olga (Slavia Occidentalis, 2013)
The paper tackles the topic of the negative or ambivalent humour in Karel Michal’s short story collection Everyday Spooks. Starting from the concepts of humour (present, e.g., in the theoretical works of Jean-Paul, Baudelaire, and Bachtin) based on the existence of negative features, the author examines the functioning of the degrading role of humour in the Czech writer’s debut volume. Carried out with these tools, the analysis of negative strategies in the humoristic writings of Michal, allows for a reinterpretation of his early texts and makes it possible to view them as perverse moralities.